Análise multitemporal da área do canal do alto Rio Paraná na porção jusante à UHE Porto Primavera - Puerta, Lorena Lucas (2011)
The deployment of the Porto Primavera dam (UHE Engenheiro Sergio Motta) influenced the region of Porto Rico (PR), the plain of the upper Paraná river, in the segment between the UHE Engenheiro Sérgio Motta and Mutum Island. The amendments made by the dam, is included to control the increase in discharges, the supply of bottom sediments was cut and transport of suspended material decreases considerably. These and other changes led the segment located downstream of the dam to begin a process of adjustment river (Souza Filho et al., 2004). The river setting is still in development and affects all the variables of river dynamics. The purpose of this study was to evaluate changes in river channel in the last three decades, giving priority to the situation in years of major floods, because these events are considered as important agents of landscape change and can make significant changes in the short space of time both in channel and the very river plain. The procedures were dealt with knowledge about the marginal erosion controls, ways of assessing its intensity, the characteristics of the tool used, the remote sensing using Landsat 5 satellite images. When analyzing the change in area between 1985-1990, it appears that the first 10 years the canal was about depositional processes and in 1995 began a string of strong changes in the channel until 1999 where the area of erosion occurred in 2004, 2005 and 2007 the channel back to ground, being on erosion processes in the years 2006 and 2010. To complement the analysis was performed regression analysis to assess the margin of error, the canal area, area of the canal and river discharge, the canal area and the permanence of river discharge, and the area of the canal and river discharge and residence before and after closure of the dam and then performed the analysis of standardized data allowing to check the reliability of the results and finally the overlay of images to identify the locations and rates of erosion. As the results, the dam construction has caused changes in the dynamics of the channel is in the years prior to its closure, either after they occur.